Determinants of Firm Value: Empirical Evidence from The Primary Consumer Goods Sector Companies - Halim, Kusuma Indawati (Jurnal Akuntansi Terapan dan Bisnis, 2024)
Investor decisions to invest in a company are partially influenced by the company's value. Investors are increasingly attracted to companies that can generate sustainable profits, ultimately enhancing the company's value. This study aims to analyze the influence of intellectual capital, profitability, leverage, and asset turnover on company value, using a sample of companies listed on the Indonesia Stock Exchange in the primary consumer products sector between 2017 and 2021. Using purposive sampling, 61 companies were selected as samples. With observations over 5 years, a total of 305 data observations were obtained. Multiple linear regression analysis was applied to secondary data sourced from the financial accounts of the selected organizations. The correlational relationship between the dependent variable and the regressors was determined by analyzing the data obtained using SPSS tools. The study results indicate that intellectual capital does not affect company value, profitability, and asset turnover positively affect company value, but leverage negatively affects company value. The positive impact of profitability and asset turnover indicates that an increase in these factors will enhance the company's value. Conversely, the negative impact of leverage suggests that an increase in leverage will decrease the company's value.